2011
DOI: 10.1111/j.1365-2109.2011.02836.x
|View full text |Cite
|
Sign up to set email alerts
|

New genetic recombination in hypervariable regions of the white spot syndrome virus isolated from Litopenaeus vannamei (Boone) in northwest Mexico

Abstract: The white spot syndrome virus (WSSV) is a pathogen of great concern to the worldwide shrimp culture. In comparative studies on the WSSV genome, regions such as the open reading frame (ORF) 14–15 and ORF 23–24, prone to deletions and recombination, had been useful to study the evolutive relationships among viral strains. When looking for the WSSV strains infecting Litopenaeus vannamei (Boone) in northwest Mexico, we found evidence of a genetic similarity in ORF 14–15 to a strain from India and a recombination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Pradeep, Shekar, Karunasagar and Karunasagar () demonstrated that Indian WSSV isolates were closely related to Thai isolates, suggesting WSSV may have been introduced to India from Thailand. Likewise, WSSV isolates from Mexico collected during 2000–2005 showed similarity in the VR14/15 region with isolates from India (Ramos‐Paredes, Grijalva‐Chon, Rosa‐Vélez & Enríquez‐Paredes, ). On the contrary, VNTR have been used to study WSSV epidemiology in small scales, such as farm‐ or pond‐level and for tracing movements between infected populations because these regions have high variation (González‐Galaviz, Rodriguez‐Anaya, Molina‐Garza, Ibarra‐Gámez & Galaviz‐Silva, ; Pradeep, Shekar, Gudkovs, Karunasagar & Karunasagar, ).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Pradeep, Shekar, Karunasagar and Karunasagar () demonstrated that Indian WSSV isolates were closely related to Thai isolates, suggesting WSSV may have been introduced to India from Thailand. Likewise, WSSV isolates from Mexico collected during 2000–2005 showed similarity in the VR14/15 region with isolates from India (Ramos‐Paredes, Grijalva‐Chon, Rosa‐Vélez & Enríquez‐Paredes, ). On the contrary, VNTR have been used to study WSSV epidemiology in small scales, such as farm‐ or pond‐level and for tracing movements between infected populations because these regions have high variation (González‐Galaviz, Rodriguez‐Anaya, Molina‐Garza, Ibarra‐Gámez & Galaviz‐Silva, ; Pradeep, Shekar, Gudkovs, Karunasagar & Karunasagar, ).…”
Section: Introductionmentioning
confidence: 82%
“…The 6031 bp deletion in VR14/15 region were also previously reported in WSSV from Thailand (WSSV‐TH‐S, 1996), the Philippines (WSSV‐PHI, 1999), Indonesia (WSSV‐INDO, 2008) (Zwart et al., ) and Vietnam (WSSV‐VN, 2003–2004) (Dieu et al., ). The unsuccessful in VR23/24 amplification were noticed in some studies, isolates from Vietnam (Dieu et al., ), India (Pradeep et al., ) and Mexico (Ramos‐Paredes et al., ) while it was proposed that the deletion of VR23/24 region extends beyond the coverage of primers designed from Asian WSSV sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, DNA extraction, quality checking and concentration estimation were performed as described previously (Ramos‐Paredes et al . ). The Vp28 gene PCR (974 bp amplicon) used primers WO001‐F and WO001‐R designed using the Primer3 software (Table ).…”
Section: Methodsmentioning
confidence: 97%
“…The seminested PCR (694‐bp amplicon) used primer WO001‐F in combination with WSSVP28‐R1 (Ramos‐Paredes et al . ) and 1 μL of the first PCR was used as template. PCR thermal cycling conditions were as described previously (Ramos‐Paredes et al .…”
Section: Methodsmentioning
confidence: 99%
“…The oligos WSSVVP28-F1: 5'-CTCGCTTGCCAATTGTCCTGT TA-3' and WSSVVP28-R1: 5'-ATTTCCACCGGC GGTAGCTGC-3' reported by Ramos-Paredes et al (2012) were used, as well as thermal cycling conditions as recommended by these authors. A negative control without DNA was used in all cases.…”
Section: Nhp-b Inoculum Preparationmentioning
confidence: 99%